Web-based Application-Assisted Academic Supervision Model in Developing PAI Teacher Competence - Filmawati, Filmawati; Nurdin, Syafrudin; Kustati, Martin; Isnaini, Muhammad (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan UIN Raden Fatah, 2023)
The purpose of this study was to describe the need for the development of academic supervision assisted by web-based applications and to develop the design of academic supervision models assisted by web-based applications in fostering teacher competence by PAI Supervisors. Teachers' competence in implementing learning at school in planning, implementing, and evaluating learning is largely determined by the coaching they receive. This research uses a type of development research (R&D) that refers to the model developed by Borg and Gall consisting of ten steps, incorporated into four main stages, namely the preliminary stage, development, field test, and dissemination stages. Data were collected using questionnaires and interviews and then processed with a descriptive statistical approach. The results showed that academic supervision in the field is still less than optimal because it is necessary to develop a website-based supervisor academic supervision model designed according to the needs of the field. The website-based academic supervision model is designed using an application called e-saga. The development of e-saga was designed using Google Workspace. The product design designed and produced at the development stage is in the form of three products, namely the design of the academic supervision model book, the design of the website-based e-saga application, and the design of the e-saga user manual. The results of validation from experts show that these three products are very valid from the aspects of content, construction, design, and language. The trial results show that the application is very feasible to use. Likewise, the practicality and effectiveness tests also show that the e-Sisaga model is very practical and effective for supervisors and teachers to use in academic supervision activities.